AB0978 Role of Bone Scan and MRI in the Detection of Bone Inflammation in Chronic Recurrent Multifocal Osteomyelitis (CRMO). (9th June 2015) - Buckley, G.; Easty, M.; Compeyrot-Lacassagne, S.; Biassoni, L.
Abstract : Background: CRMO is a rare inflammatory bone disorder presenting with relapsing and remitting episodes of bone pain. It affects predominantly females between the age of 9 and 14. Insidious onset of bone pain in one or multiple sites may be associated with localised swelling and warmth. Objectives: To assess the value of bone scan (BS) and MRI in the detection of bone inflammation. To correlate the imaging findings with inflammatory markers and clinical symptoms/location of pain. Methods: We performed a retrospective review of the clinical notes of children with a confirmed diagnosis of CRMO who had both bone scan and MRI between September 2009 to September 2014 and within 9 weeks of each other. We recorded for each patient: inflammatory markers at time of scans (ESR, CRP and WCC), clinical symptoms/location of pain. Patients were excluded if both scans were done more than 9 weeks apart or if there was any change to treatment in-between scans. We recorded for both bone scan and MRI the number and the location of lesions. Results: We identified nine patients (7 females, 2 males) who had CRMO and both bone scan and MRI less than 9 weeks apart. Despite a retrospective design and a small data set, we could observe that inflammatory markers appear non-specific, pain is often associated with a bone lesion on imaging, there are many additional asymptomatic lesions, pain can be referred, MRI and BS are equivalent in 44% of cases, there is no false negatives with BS, MRI is consistently detecting more lesions, BS may be better at detecting lesions in ribs and MRI detects more lesions in the spine. Conclusions: The nature of these additional lesions seen on MRI is questionable as it is known that bone marrow oedema can be seen in normal children. Specificity and clinical importance of the MRI-positive but bone scan-negative lesions are still contentious issues. High quality BS is essential, with spot view and the right level of reporter experience. BS remains more easily accessible than MRI and contributes to the diagnosis of CRMO. Further studies are needed to establish sensitivity and specificity of both imaging. Disclosure of Interest: None declared